Corilagin alleviates intestinal ischemia/reperfusion-induced intestinal and lung injury in mice via inhibiting NLRP3 inflammasome activation and pyroptosis - Li, Wenlian; Yang, Kejia; Li, Bin; Wang, Yunxiang; Liu, Jing; Chen, Dapeng; Diao, Yunpeng (Frontiers in Pharmacology, 2022)
Intestinal ischemia reperfusion (II/R) is a clinical emergency that frequently occurs in a variety of clinical conditions. Severe intestinal injury released cytotoxic substances and inflammatory mediators which can activate local inflammatory response and bacteria translocation and trigger multi-organ failure including lung injury which is common complications of II/R injuries and contributes to high mortality rate. Corilagin (Cor) is a natural ellagitannin found in a variety of plants and has been shown many biological and pharmacological properties such as antioxidant, anti-inflammatory, anti-apoptosis. However, no studies have reported the effects and molecular mechanisms of Cor in alleviating II/R-induced intestinal and lung damage. In this study, Cor was found to significantly alleviate II/R-induced pathological damage, inflammatory response, oxidative stress, NLRP3 inflammasome activation, and pyroptosis in intestinal and lung tissues both in vivo and in vitro. Further, Cor also inhibited LPS/Nigericin-induced NLRP3 inflammasome activation and pyroptosis in RAW264.7, MLE-12, and IEC-6 cells, indicates an amelioration of Cor in II/R-induced intestinal and lung injury via inhibiting NLRP3 inflammasome activation and pyroptosis. Thus, Cor might be a potential therapeutic agent for II/R-induced inflammation and tissue injuries.